2002
DOI: 10.1007/s00147-002-0469-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved specificity and sensitivity when using pronase-digested lymphocytes to perform flow-cytometric crossmatch prior to renal transplantation

Abstract: Several laboratories have resorted to flow-cytometric crossmatch (FCXM) in an effort to prevent hyperacute and accelerated renal allograft rejections. The currently employed FCXM has problems with both false-positive and -negative reactions, largely as a result of irrelevant IgG binding to Fc IgG receptors. In 1980, we circumvented this problem by digesting Fc IgG receptors with pronase, and demonstrated that, with immunofluorescence microscopy (IF), detection of IgG anti-HLA antibodies was highly sensitive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In cell characterization by surface markers, the use of pronase may not be preferred as it may damage the surface proteins due to its relatively low substrate specificity. A number of studies have been performed to investigate the effect of pronase in different applications and reported that proteases affected the cell properties of Lymnaea neurons, extracellular matrix of chondrocytes, lipopolysaccharide receptor of Kupffer cells, and Fc IgG receptors, CD16 and CD32 of lymphocytes (details given in the supplementary file). Thus we also tested the effect of pronase on surface antigens using human mesenchymal stem cells (MSC) from bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…In cell characterization by surface markers, the use of pronase may not be preferred as it may damage the surface proteins due to its relatively low substrate specificity. A number of studies have been performed to investigate the effect of pronase in different applications and reported that proteases affected the cell properties of Lymnaea neurons, extracellular matrix of chondrocytes, lipopolysaccharide receptor of Kupffer cells, and Fc IgG receptors, CD16 and CD32 of lymphocytes (details given in the supplementary file). Thus we also tested the effect of pronase on surface antigens using human mesenchymal stem cells (MSC) from bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,16 During this time, evidence has accumulated to indicate that this assay is more sensitive than conventional CDC techniques, may detect antibodies which are undetected by other routine crossmatch methods, and may provide important predictive information regarding patient risk and 30 However, this information is complicated by clinical, methodological, and analytical differences between reports. Variable inter-laboratory consensus and false-negative rates point to concerns of assay precision and specificity 30,31 that may reflect differences in methodology or equipment, 30,[32][33][34] in operator technique, or in criteria for defining a positive result in different centers. 33,35,36 In the absence of clear evidence founded on prospective-blinded studies, the objective prognostic performance of FCXM remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry crossmatching was performed on the day of transplantation with a current serum sample. Briefly, donor cells treated with pronase (1 mg/dL) were incubated with a patient's serum, and HLA antibodies were detected with fluorescein isothiocyanate–conjugated goat [F(ab)′ 2 ] anti‐human immunoglobulin G (IgG; Fc‐specific) and acquired with FACSCalibur. Anti‐CD3 peridinin chlorophyll protein and anti‐CD19 R‐phycoerythrin (BD Biosciences) were used to gate T and B cell populations, respectively.…”
Section: Methodsmentioning
confidence: 99%